2014
DOI: 10.1653/024.097.0333
|View full text |Cite
|
Sign up to set email alerts
|

Oncideres ocularis(Coleoptera: Cerambycidae) GirdlingMimosa bimucronata(Fabaceae) in Brazil

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The process of Diastocera trifasciata attack on branches described in this study is similar to that observed in the genus Oncideres Lepeletier de Saint Fargeau & Audinet-Serville (Cerambycidae: Lamiinae) [ 24 , 25 , 26 , 27 , 28 ]. However, differences were observed in the number of individuals attacking the branch and the size of the branches attacked.…”
Section: Discussionsupporting
confidence: 83%
“…The process of Diastocera trifasciata attack on branches described in this study is similar to that observed in the genus Oncideres Lepeletier de Saint Fargeau & Audinet-Serville (Cerambycidae: Lamiinae) [ 24 , 25 , 26 , 27 , 28 ]. However, differences were observed in the number of individuals attacking the branch and the size of the branches attacked.…”
Section: Discussionsupporting
confidence: 83%
“…The Mimosa genus belongs to the Fabaceae family of legumes (subfamily: Mimosoideae ) and consists of almost 400 species of shrubs and herbs [ 1 ]. The species are distributed mainly in Bangladesh, Indonesia, Malaysia, Japan, India, Pakistan, Sri Lanka, China, Cambodia, Taiwan, Africa (Nigeria, Mauritius, and Reunion Island), Australia, Brazil, Venezuela, Mexico, Philippines, Cuba, northern Central America, Paraguay, Argentina, Uruguay, Thailand, several Pacific Islands, Papua New Guinea, and North America [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Figure 1 presents the ethnogeographical distribution of the Mimosa species in different countries of the world.…”
Section: Introductionmentioning
confidence: 99%
“…The length of the S. adstringens branches girdled by O. saga, was shorter than those of O. puberula by O. cervina, 282 ± 0.87 cm (Witeck Neto et al, 2015), P. pyrifolia by O. dejeanii, 331 ± 0.17 cm (Cordeiro et al, 2010) and longer than those of M. bimucronata by O. ocularis, 126.72 ± 11.09 cm (Lemes et al, 2014a).…”
Section: Discussionmentioning
confidence: 82%
“…F.) Naka (Rosaceae), 3.47 ± 0.15 cm (Cordeiro et al, 2010) and Oncideres ocularis (Thomson) in Mimosa bimucronata (DC.) Kuntze (Fabaceae), 8.26 ± 0.84 mm (Lemes et al, 2014a) in Viçosa, Minas Gerais, Brazil.…”
Section: Discussionmentioning
confidence: 99%